2019
DOI: 10.1051/0004-6361/201935571
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of red clump stars does not support the X-shaped Galactic bulge

Abstract: Context. Claims of an X-shaped Galactic bulge were based on the assumption of red clump stars as standard candles in some lines of sight crossing the off-plane bulge. However, some doubts have been cast on whether the two peaks in star counts along the line of sight really represent a double peak in the density distribution, or whether there is something wrong with the assumption of a unique constant absolute magnitude for all of these stars. Aims. With the advent of Gaia-DR2 parallaxes in combination with nea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…Also, based on unWISE (Lang 2014) 3.4 and 4.6 μm wide-field images, Ness & Lang (2016) identified and quantified (Ciambur et al 2017) the X/peanut(P)-shaped structure. However, López-Corredoira (2016), Lee et al (2018), andLópez-Corredoira et al (2019) do not confirm the discovery of the X-shape structure based on the population of the double red clump. In addition to that, as stressed by López-Corredoira (2017), oxygen-rich Mira variables (also used as standard candles) match a boxy, but not an X-shape bulge.…”
mentioning
confidence: 95%
“…Also, based on unWISE (Lang 2014) 3.4 and 4.6 μm wide-field images, Ness & Lang (2016) identified and quantified (Ciambur et al 2017) the X/peanut(P)-shaped structure. However, López-Corredoira (2016), Lee et al (2018), andLópez-Corredoira et al (2019) do not confirm the discovery of the X-shape structure based on the population of the double red clump. In addition to that, as stressed by López-Corredoira (2017), oxygen-rich Mira variables (also used as standard candles) match a boxy, but not an X-shape bulge.…”
mentioning
confidence: 95%
“…Recent mappings of the inner and outer bulge regions with RC stars from the Vista Variables in the Via Lactea (VVV) survey by Wegg & Gerhard (2013) and Wegg et al (2015) have further confirmed the B/P nature of the inner bulge that proceeds to extend and flatten into a barred structure into the disk, both structures oriented at an angle of ∼ 27 • . Whilst this interpretation has been contested with López-Corredoira et al (2019) claiming that the split RC is a result of two distinct stellar populations, the spectacular WISE imaging of Ness & Lang (2016) reveals the X-shape clearly. The proper motion data from VVV as analyzed by Sanders et al (2019a) show differential motion between the peaks, which argues strongly against population effects causing the X-shape.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in § 1, these and other authors contend that the double red clumps trace out an "X"-shaped structure, and 0.0 2.0 4.0 that the two clumps reside at the near (∼ 6.5 kpc) and far (∼ 8.8 kpc) ends of the bar. However, other explanations relating to chemical composition variations, particularly involving He enhancements, have also been suggested (e.g., Lee et al 2015;Joo et al 2017;Lee et al 2018Lee et al , 2019López-Corredoira et al 2019). 17 also shows that the red clump (g − i) o dispersion is relatively small, and that the bright and faint red clumps effectively span the same color range.…”
Section: Bulge Cmds and The Double Red Clumpmentioning
confidence: 96%